A diagnostic in vitro urine assay for interstitial cystitis - Keay, S.; Zhang, C.-O.; Hise, M.K.; Hebel, J.R.; Jacobs, S.C.; Gordon, D.; Whitmore, K.; Bodison, S.; Gordon, N.; Warren, J.W. (Urology (Ridgewood, N.J.), 1998)
Objectives. A low molecular weight urine factor that inhibits the proliferation of normal bladder epithelial cells in vitro was previously shown to be present significantly more often in the urine of patients with interstitial cystitis (IC) than in the urine of asymptomatic age-, race-, and sex-matched control subjects. We sought to determine the specificity of this finding for IC by determining whether the urine of patients with other urogenital inflammatory disorders also contains a factor that inhibits bladder epithelial cell proliferation. Methods. Urine was collected from women with IC, acute bacterial cystitis, or vulvovaginitis, as well as from asymptomatic control women. The proliferation of primary normal adult bladder epithelial cells was determined by measuring 3H-thymidine incorporation in vitro. Results. Osmolality- and pH-corrected urine specimens from 50 (86%) of 58 women with IC significantly inhibited human bladder epithelial cell proliferation compared with 3 (8%) of 36 asymptomatic control women, 7 (12%) of 58 women with bacterial cystitis, and 0 (0%) of 12 women with vulvovaginitis (P < 0.001 for the comparison of mean percent change in 3H-thymidine incorporation with IC urine versus urine from each of the control groups). Optimal sensitivity and specificity values of 91.4% and 90.6%, respectively, were achievable at a cutoff of 25% inhibition of 3H-thymidine incorporation, using all three control groups. Conclusions. The measurement of urine antiproliferative activity may be a useful noninvasive means for diagnosing IC in women.